Contamination by antimicrobial-resistant enterobacteria isolated from cell phones and hands in a veterinary hospital - Hespanha, Ana Carolina Valentim [UNESP]; Minto, Bruno Watanabe [UNESP]; Cardozo, Marita Vedovelli [UNESP]; Menezes, Mareliza Possa De [UNESP]; Tasso, Júlia Banhareli [UNESP]; Moraes, Paola Castro [UNESP] (Akademiai Kiado Zrt., 2021)
Hospital infections are of great relevance in human and animal health, and fomites are important in the spread of pathogens in hospital units. The aim of this study was to investigate the frequency of enterobacteria in the operating room of a veterinary hospital, the potential cross-contamination of samples, and to characterise the susceptibility profile of the isolates to antimicrobials. Sixty-five samples were collected from five different surgical procedures. These samples came from the hands and cell phones of the surgical team and pet owners, operating tables, and patients. Species detection was performed through polymerase chain reaction, genetic diversity by pulsed-field gel electrophoresis (PFGE), and susceptibility to antimicrobials through an antibiogram. Escherichia coli and Proteus mirabilis isolates were obtained from eight samples, from the hands of the anaesthesiologist, the pet owner, and the surgeon; the surgeon's, the nurse's and the anaesthesiologist's cell phones, and two surgical tables. Furthermore, PFGE showed high genetic diversity among the isolates, which showed multidrug resistance. The identification of multidrug-resistant E. coli and P. mirabilis on cell phones of the surgical team is a major concern and, although no direct correlation was found, the isolation of these bacteria inside the clean area of the operating room shows the possibility of nosocomial transmission from cell phones to susceptible patients.
Keywords: fomites; nosocomial infection; pulsed field gel electrophoresis; small animals; surgery centre